Фитохимическое изучение биологически активных соединений Achillea micranthoides Klok. - Дуюн, И. Ф.; Дуюн, Ірина Федорівна (БГМУ, 2018)
Перспективным растительным источником для получения современных фитопрепаратов являются виды рода Achillea L. Биологическая активность перспективного вида Achillea micranthoides Klok. связана с накопленим эфирного масла (до 3,11+0,28%) и филлохинона (витамин К1) (до 3,92+0,19%). Присутствие и содержание этих веществ установлено методами ТCХ, ГХ-МС, спектрофотометрии. Трава Achillea micranthoides Klok. перспективна для заготовки в биоценозах и возделывания в специализированных хозяйствах для получения новых лекарственных средств. The perspective herbal source for the receipt of the modern herbal preparations there are species of Achillea L. genus. The biological activity of perspective specie of Achillea micranthoides Klok. is related with accumulation in herbal raw material of essential oils (up to 3,11+0,28%) and phylloquinone (vitamin К1) (up to 3,92+0,19%). The presence and content of these substances is established by the methods of TLC, GC-MS, Spectrophotometry. The herbal raw material of Achillea micranthoides Klok. specie is promising for harvesting in biocenoses and cultivation in specialized farms for obtaining new herbal drugs.
Keywords: тысячелистник подовый; эфирное масло; витамин К1; трава; газовая хроматография; спектрофотометрия